The sins of Scripture : exposing the Bible's texts of hate to reveal the God of love - Spong, John Shelby (HarperSanFrancisco, 2005)
An exploration of biblical passages that are used to justify discrimination, oppression, and violence against minorities, members of other faiths, and the environment seeks to reveal and recover the texts' ultimate depth and purpose.